STUDENTS’ MOTIVATION IN LEARNING HISTORY THROUGH THE COOPERATIVE LEARNING MODEL OF THE NUMBERED HEADS TOGETHER TYPE AMONG GRADE X2 STUDENTS AT SMA NEGERI 4 KOTA GORONTALO - Eka Prasetia Ahmad; Resmiyati Yunus; Naufal Raffi Arrazaq (CV. Fahr Publishing, 2025)
This study aimed to optimize the motivation to learn history among class X-2 students at SMA Negeri 4 Gorontalo City through the implementation of the Numbered Heads Together (NHT) cooperative learning model. Using a qualitative approach, data were obtained through observation, in-depth interviews with educators and students, and analysis of related documentation. Data were analyzed descriptively to map the dynamics of changes in student motivation. The results of pre-cycle observations showed that student learning motivation was at 62%, reflecting a low level of focus. After the NHT model intervention in cycle I, there was a significant increase to 90% (very good category), marked by increased active participation, enthusiasm in discussions, and students' readiness to respond to questions without the need for direct instruction. These findings indicate that the NHT model is an effective instrument in fostering student motivation and collective involvement in history learning.